Platelet-rich plasma accelerates skin wound healing by promoting re-epithelialization. Issue 1 (14th August 2020) - Xu, Pengcheng; Wu, Yaguang; Zhou, Lina; Yang, Zengjun; Zhang, Xiaorong; Hu, Xiaohong; Yang, Jiacai; Wang, Mingying; Wang, Binjie; Luo, Gaoxing; He, Weifeng; Cheng, Biao
Abstract: Background: Autologous platelet-rich plasma (PRP) has been suggested to be effective for wound healing. However, evidence for its use in patients with acute and chronic wounds remains insufficient. The aims of this study were to comprehensively examine the effectiveness, synergy and possible mechanism of PRP-mediated improvement of acute skin wound repair. Methods: Full-thickness wounds were made on the back of C57/BL6 mice. PRP or saline solution as a control was administered to the wound area. Wound healing rate, local inflammation, angiogenesis, re-epithelialization and collagen deposition were measured at days 3, 5, 7 and 14 after skin injury. The biological character of epidermal stem cells (ESCs), which reflect the potential for re-epithelialization, was further evaluated in vitro and in vivo . Results: PRP strongly improved skin wound healing, which was associated with regulation of local inflammation, enhancement of angiogenesis and re-epithelialization. PRP treatment significantly reduced the production of inflammatory cytokines interleukin-17A and interleukin-1β. An increase in the local vessel intensity and enhancement of re-epithelialization were also observed in animals with PRP administration and were associated with enhanced secretion of growth factors such as vascular endothelial growth factor and insulin-like growth factor-1. Moreover, PRP treatment ameliorated the survival and activated the migration and proliferation of primary cultured ESCs, and these effects were accompanied by the differentiation of ESCs into adult cells following the changes of CD49f and keratin 10 and keratin 14. Conclusion: PRP improved skin wound healing by modulating inflammation and increasing angiogenesis and re-epithelialization. However, the underlying regulatory mechanism needs to be investigated in the future. Our data provide a preliminary theoretical foundation for the clinical administration of PRP in wound healing and skin regeneration.